Determinants of FDI in France: Role of transport infrastructure, education, financial development and energy consumption. (28th October 2020) - Shahbaz, Muhammad; Mateev, Miroslav; Abosedra, Salah; Nasir, Muhammad Ali; Jiao, Zhilun
Abstract: This article explores the effect of education and transportation infrastructure on foreign direct investment for the French economy over the period of 1965–2017. Economic growth, financial development and electricity consumption are also considered as additional determinants of foreign direct investment. In so doing, the SOR unit root test is applied in order to examine unit root properties of variables in the presence of sharp and smooth structural breaks in the series. To examine the presence of cointegration between the variables, the bootstrapping ARDL cointegration test is applied. The empirical results show the presence of cointegration between the variables. Education and transportation add to foreign direct investment. Financial development declines foreign direct investment. The relationship between electricity consumption (economic growth) and foreign direct investment is bidirectional. The nonlinear relationship between education (transportation infrastructure) and foreign direct investment is U‐shaped.